Contribution to the genus Chrysidea Bischoff, 1913 from China, with description of a new species (Hymenoptera, Chrysididae) - Rosa, Paolo; Xu, Zai-Fu (Zootaxa, 2015)
The genus Chrysidea Bischoff, 1913 belongs to the tribe Chrysidini (Hymenoptera, Chrysididae). Bohart (1988) revalidated the genus after it was considered as subgenus of Chrysis Linnaeus, 1761 (Linsenmaier 1959) or Trichrysis Lichtenstein, 1876 (Kimsey & Bohart 1981) and synonymised it with Chrysis (Trichrysis) (Linsenmaier 1984). Kimsey & Bohart (1991) gave a checklist of 19 known species of Chrysidea, of which three are known from the Oriental Region, C. bidenticulata (Mocsáry, 1913), C. furiosa (Cameron, 1897) and C. monticellii (du Buysson, 1906). Only one species, C. pumila (Klug, 1845), has been recorded for the Palaearctic part of China (Hammer 1936; Rosa et al. 2014).